Implementation of Active Learning Student Created Case Studies with Flip Chart to Increase Self Directed Biology Learning in XI IPA 4 Class of SMA Negeri 4 Surakarta in Academic Year 2009/2010 - Suci Kusuma Dewi; Slamet Santosa; Muzayyinah Muzayyinah (BIO-PEDAGOGI, 2013)
This research own the target to increase self directed learning the student in biological  study with applying  active  learning of Student-Created Case  Studies accompanied by  Flip Chart  in class  of  XI  IPA  4 SMA  Country  4 Surakarta  of teaching year 2009/2010. This  research represent  the  research of  claas  action (Classroom  Action Research) consited of two cysle.  Every cycle consisted of 4 phase taht is planning, acting, observing, and reflecting.  Subject research is student of class XI IPA 4 SMA Contry  4  Surakarta  of teaching  year 2009/2010. Technique  of data  complier used cover the enquette, observation, and interview.  Data analysis used in this research is technique analisyse consited of the data reduction, data presetation, an withdrawal of conclusion or verivication. Result  of research  indicate  taht  the  applying  active  larning  of Student-Created  Case  Studies  accompanied by  Flip Chart  can improve  the  self directed learning the student in biologycal study.  Make-up of self directed learning the visible student  passing  result  of enquette  and observation.   Mean  assess  the  performance percentase  every  indicator from  self directed learning  obsevation the  student at  pre cycle is 14,68%, cycle I equal to 41,57%, and cycle II equal to 77,73.  Mean assess the  performance  percentase every  indicator from  self  directed  learning  enquette the student at pre cycle equal to 74,40%, cycle I equal to 79,74%, and cycle II equal to 80,29%.  Its conclusion that applying active larning of Student-Created Case Studies accompanied by Flip Chart can improve the self directed learning. Key Words: Student-Created Case Studies, Flip Chart, Self Directed Learning